2018
DOI: 10.19126/suje.322791
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Yayınlanmış FeTeMM Eğitimi İle İlgili Çalışmaların İncelenmesi

Abstract: Öz. Bu çalışmanın amacı Fen Teknoloji Mühendislik ve Matematik yaklaşımı (FeTeMM) içerikli makaleleri ve lisansüstü çalışmaları yöntem ve konu eğilimi bakımından incelemektir. Bu doğrultuda, araştırmada yer alan çalışmalar Ulusal Akademik Ağ ve Bilgi Merkezi (ULAKBİM), Education Resources Information Center (ERIC), EBSCO Host, International Scientific Indexing (ISI) Web of Science ve Scopus veritabanları tarafından taranan ve internet üzerinden erişime açık olan 30 makale ve ikisi kısıtlı erişimde bulunmak üze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
(5 reference statements)
0
10
0
9
Order By: Relevance
“…When we look at the national literature, there are different studies about researchers STEM education. When we look at the national literature, there are studies on the STEM field as a whole (Elmalı andBalkan-Kıyıcı, 2017, Tezel andYaman, 2017) These studies include STEM scale development, Cooperative STEM Education is to determine the perception of Chemistry and Mathematics Teacher Candidates to STEM education, STEM integration to determine the effect of fifth grade students in secondary school science concepts, The evaluation of in-service training for science teachers to be able to realize STEM education, Improvement of STEM activity, The impact of STEM education on students' scientific process skills and science lectures, Through the STEM training, it has been shown that individuals make a better learning by doing business association and contribute to the development of creativity skills, STEM education has improved the success of students' found that teachers' STEM readiness was not enough.It has been determined that articles and graduate studies which have been done in recent years are not given as a whole in these studies and general orientations are not found in the studies. With this study, this deficiency was tried to be solved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we look at the national literature, there are different studies about researchers STEM education. When we look at the national literature, there are studies on the STEM field as a whole (Elmalı andBalkan-Kıyıcı, 2017, Tezel andYaman, 2017) These studies include STEM scale development, Cooperative STEM Education is to determine the perception of Chemistry and Mathematics Teacher Candidates to STEM education, STEM integration to determine the effect of fifth grade students in secondary school science concepts, The evaluation of in-service training for science teachers to be able to realize STEM education, Improvement of STEM activity, The impact of STEM education on students' scientific process skills and science lectures, Through the STEM training, it has been shown that individuals make a better learning by doing business association and contribute to the development of creativity skills, STEM education has improved the success of students' found that teachers' STEM readiness was not enough.It has been determined that articles and graduate studies which have been done in recent years are not given as a whole in these studies and general orientations are not found in the studies. With this study, this deficiency was tried to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…FeTeMM eğitimi, 21. yüzyılda yenilikçi ve yaratıcı düşünme becerilerine sahip bir nesil yetiştirmeyi amaçlayan ülkeler tarafından benimsenmiştir (Bybee, 2010). Ülkemizde de FeTeMM eğitimi çalışmaları 2014 yılından sonra hız kazanmış ve FeTeMM eğitimi çalışmalarının amacı, ele alınış biçimi ve uygulama yöntemlerinin incelemesi yapılmıştır (Elmalı ve Balkan-Kıyıcı, 2017…”
unclassified
“…The other items are related to the subjects that the teachers had not been trained before and did not use. 2466 The Readiness Level of Teachers in Science, Technology, Engineering and Mathematics Education Items 1,6,7,8,10,11,13,18,19,20,23,25,31 ve 32 show significant differences according to branch variable (p<0,05).…”
Section: Findings the Findings On The Readiness Of The Teachers In Stmentioning
confidence: 99%
“…The Ministry of National Education has included the STEM Education partly by including engineering practices and design skills in secondary school science program. Studies conducted in Turkey show that STEM education has positive effects in certain elements like the attitudes, motivations, interests, and scientific process skills of students [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation